Effects of COVID-19 on Learners’ Wellbeing in a Rural High School District - Patricia Sentle Mofokeng (International Journal of Studies in Psychology)
In December 2019, COVID-19 quickly spread across various regions, and its effects devastated the educational system globally and locally. The wellbeing of learners has been linked to various aspects of their lives, such as their mental health and academic performance. Therefore, this study investigates the effects of COVID-19 on learners’ wellbeing in a rural high school. It adopted a qualitative approach and phenomenology research design within the interpretive paradigm. Data were generated from telephone in-depth interviews using the WhatsApp social media platform as participants were isolated due to the lockdown regulations that had been imposed as a result of the pandemic. Six learners and two teachers were purposively selected from a rural high school in the Thabo Mofutsanyane District of the Free State province. Data were analysed using thematic analysis. The findings revealed that poor academic performance, loss of loved ones, learners developing mental health issues, and the “new normal” could be the effects of COVID-19, which could affect the learners’ wellbeing. This study recommended that teachers and learners should be trained to gain the digital skills and knowledge needed for successful teaching and learning on online platforms in cases such as the COVID-19 pandemic.